A Cost Effective Technique for Vacuum-assisted Closure Therapy With a Portable Suction System. Issue 1 (March 2016) - Albayrak, Akif; Balioğlu, Mehmet B.; Kargin, Deniz; Yavuz, Umut; Atici, Yunus; Gursu, Sukru S.
Abstract : Vacuum-assisted wound-closure therapy is applied to an open wound to create subatmospheric pressures within a sealed dressing. The therapy increases blood flow, decreases edema and bacterial count, and enhance the formation of granulation tissue. It has been used successfully in treating open wounds of the extremities, sternum, and abdominal wall and also pressure or diabetic ulcerative wounds. Patients who needed open wound treatment before surgical closure were included in this study. Healing was determined by development of a clean granulating wound bed (ready for skin grafting) and reduction of wound surface area. The pressure applied creates a suction force that removes excess fluid and debris, decreases bacterial levels of tissue, and increases tissue perfusion, which results in improved wound healing. In our technique, the system consists of a sterilized simple foam sponge, a vacuum drain, 2 blood infusion kits, a negative pressure aquarium air pump, 1 L saline bottle, and a sterile drape. With the technique we are presenting, vacuum-assisted wound-closure therapy can be applied in a similar and cost-effective way.